Optimizing The Utilization of Betung Bamboo by Straightening and Preservation Techniques in Bangunsari Village, Tanjung Morawa District, Deli Serdang Regency, Sumatera Utara - Surya Dharma; Angga Bahri Pratama; Ferry Fachrizal; Dina Tri Septiningtiyas; Mardiana Mardiana; Ts. Harun Bin Sahat; Noor Aisyah Binti Mohd Zahar; Wan Fadhilah Bin Wan Hitam (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The existence of bamboo in Indonesia is very abundant; in fact, it is easy to find bamboo in almost every region of Indonesia. In general, the shape of bamboo construction is not completely straight, so some people do not use bamboo as a pole or supporting material for building or construction purposes. From various studies, bamboo structures have been proven to have many advantages. It’s tough and elastic fibers are very good at withstanding loads (both compressive/tensile, shear, and bending loads). This service aims to provide information, understanding, and skills to the community about how to process and use bamboo for various purposes, especially for building poles and plant cultivation places. The technique is by straightening the shape of the bamboo so that the straightened bamboo can be used on a wider scale. Bamboo is straightened with a simple machine with the help of fire, so that the bamboo is easier to process. After the bamboo is straightened with the help of a machine equipped with a hydraulic device and heated using fire, the added value of the bamboo increases and can be used more widely.